2005
DOI: 10.1161/circulationaha.104.475277
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional and Real-Time Three-Dimensional Echocardiographic Fetal Diagnosis of Aorto-Ventricular Tunnel

Abstract: A 22-gestational-week-old female fetus was referred to our prenatal echocardiographic unit to evaluate her left ventricular dilatation and dysfunction. An aorto-ventricular tunnel was visualized (Figure 1a and 1b), causing marked left ventricular diastolic overload, overt fetal heart failure, hydrops, and polidramnios. The mother was informed about the possibility of spontaneous abortion or premature delivery, and the pregnancy was closely monitored with serial fetal echographic and echocardiographic evaluatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 0 publications
3
12
0
Order By: Relevance
“…The combination of a defect between aorta and pulmonary artery with two normal semilunar valves is the typical echocardiography finding in APW, the short axis view of the aortopulmonary septum in a perpendicular plane being very helpful to diagnose APW. Other signs such as dilation of the cardiac outlets or pulmonary regurgitation are only indirect clues to the presence of APW [3,8,9] . It may sometimes be difficult to differentiate APW from truncus arteriosus in APW type III [5] .…”
Section: Discussionmentioning
confidence: 99%
“…The combination of a defect between aorta and pulmonary artery with two normal semilunar valves is the typical echocardiography finding in APW, the short axis view of the aortopulmonary septum in a perpendicular plane being very helpful to diagnose APW. Other signs such as dilation of the cardiac outlets or pulmonary regurgitation are only indirect clues to the presence of APW [3,8,9] . It may sometimes be difficult to differentiate APW from truncus arteriosus in APW type III [5] .…”
Section: Discussionmentioning
confidence: 99%
“…Transthoracic cross-sectional imaging in a parasternal long-axis view, sometimes with clockwise rotation of the probe [ 11 , 39 ] demonstrates the tunnel itself, as well as its aortic origin and left ventricular opening. Both two-dimensional and real-time three dimensional echocardiography have also established reliable fetal diagnosis [ 40 - 42 ]. On color-Doppler studies, diastolic flow is seen passing from the aorta to the left ventricle, and systolic, from the ventricle to the aorta.…”
Section: Diagnostic Methodsmentioning
confidence: 99%
“…Hypertrophy and dilatation of the left ventricle with progressive reduction of its shortening fraction are consistent features, and there is often disproportionate dilatation of the aortic root with apparent incompetence of the valve. Using color flow Doppler imaging, blood flow around the aortic valve has been demonstrated [ 16 , 42 ], as well as flow specifically within the tunnel itself [ 40 , 41 ]. There are no known molecular markers for aorto-ventricular tunnel at present, and it is not associated with any recognized genetic syndrome.…”
Section: Antenatal Diagnosismentioning
confidence: 99%
“…However, one case died after surgery because heart failure did not improve. Three cases did not develop heart failure during the fetal period, but surgical repair was performed on all cases [3][4][5][6][7][8][9]. Martins et al [1] reported that eight of 11 cases of ALVT developed heart failure within 6 months after birth.…”
Section: Discussionmentioning
confidence: 98%